Dopaminergic Neurons Transplanted Using Cell‐Instructive Biomaterials Alleviate Parkinsonism in Rodents. (3rd September 2018) - Adil, Maroof M.; Rao, Antara T.; Ramadoss, Gokul N.; Chernavsky, Nicole E.; Kulkarni, Rishikesh U.; Miller, Evan W.; Kumar, Sanjay; Schaffer, David V.
Abstract: Cell replacement therapy (CRT) is a promising treatment for degenerative disorders, such as Parkinson's disease (PD). However, CRT is in general hindered by poor graft survival, limited cell dispersion, modest cell integration, and delayed therapeutic efficacy. These challenges need to be addressed to enhance the clinical translation of CRT. Here, key bioactive factors that increase the survival and dispersion of human pluripotent stem cell‐derived midbrain dopaminergic (mDA) neurons, the primary type of cells lost in PD, are identified. mDA neurons cotransplanted with survival and dispersion factors within a protective hyaluronic acid hydrogel, optimized for controlled factor release and cell spread, alleviate disease symptoms in PD model rats. Importantly, treatment benefits correlate with increased graft survival, dispersion, and integration. Optimally engineered cell‐instructive transplantation platforms thus offer promise for enhancing CRT in PD and potentially a range of degenerative diseases or trauma. Abstract : Midbrain dopaminergic neurons derived from human pluripotent stem cells and encapsulated in a hydrogel‐based transplantation platform, which also incorporated factors that are capable of promoting graft survival, dispersion, and integration, enhance therapeutic efficacy upon implantation into a rodent model of Parkinson's disease.